Potential of Extract of Tamarindus Indica L Leaves an Anti-Inflammatory on Carrageenan Induced Wistar Rats - Wati, Aulia; Sukmawati, Sukmawati; Putra, Bayu (Faculty of Pharmacy, Universitas Muslim Indonesia, 2023)
Tamarind leaves are used in traditional medicine for inflammation, stomach pain, rheumatism, and sore throats. The aims of this study was to determined the potential of extract tamarind leaf as an anti-inflammatory in Wistar rats. This study was used experimental rats divided into 5 groups, namely group I was given Na. CMC, group II was given diclofenac sodium dose of 5.136 mg/kgBW, groups III, IV, and V were given ethanol extract of tamarind leaves at a doses of 250, 500 and 1000 mg/kgBW. The test animals induced with 1% lambda carrageenan by intraplantar after one hour given test preparation orally. Measurements of edema volume and thickness of the rats were carried out before and after induction for 7 hours at 1 hour intervals using a pletysnometer and calipers. The research data was calculated statistically using the one way anova test and Post Hoc LSD. The results of the study showed that the extract group at a dose of 1000 mg/kgBW had an anti-inflammatory effect not significantly different compared to the diclofenac sodium group at a dose of 5.136 mg/kgBW. Therefore, obtained results showed that the extract of tamarind leaf has an anti-inflammatory effect with an effective dose of 1000 mg/kgBW.